2016
DOI: 10.3390/ijerph13060566
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceived Heat-Health Symptoms Increased with Warmer Classroom Temperatures

Abstract: Temperatures in Africa are expected to increase by the end of the century. Heat-related health impacts and perceived health symptoms are potentially a problem, especially in public schools with limited resources. Students (n = 252) aged ~14–18 years from eight high schools completed an hourly heat-health symptom log over 5 days. Data loggers measured indoor classroom temperatures. A high proportion of students felt tired (97.2%), had low concentration (96.8%) and felt sleepy (94.1%) during at least one hour on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…They may spend more time outdoors, especially if indoors is warmer than outdoors, as has occurred in dwellings in urban Johannesburg [59]. Similarly, in schools where shipping containers are being used as classrooms, indoor temperatures can exceed 40 • C [60]. In such hot conditions, schoolchildren experience tiredness and breathing difficulties and teachers may prefer to take children outdoors [60].…”
Section: Climate Change and Skin Cancer In Southern Africamentioning
confidence: 99%
See 1 more Smart Citation
“…They may spend more time outdoors, especially if indoors is warmer than outdoors, as has occurred in dwellings in urban Johannesburg [59]. Similarly, in schools where shipping containers are being used as classrooms, indoor temperatures can exceed 40 • C [60]. In such hot conditions, schoolchildren experience tiredness and breathing difficulties and teachers may prefer to take children outdoors [60].…”
Section: Climate Change and Skin Cancer In Southern Africamentioning
confidence: 99%
“…Similarly, in schools where shipping containers are being used as classrooms, indoor temperatures can exceed 40 • C [60]. In such hot conditions, schoolchildren experience tiredness and breathing difficulties and teachers may prefer to take children outdoors [60]. This may lead to increased exposure to the sun and possibly increase skin cancer risk.…”
Section: Climate Change and Skin Cancer In Southern Africamentioning
confidence: 99%
“…Further, many school classrooms in the country are constructed of prefabricated asbestos sheeting and corrugated iron roofs or made from converted shipping containers. A study in several parts of Johannesburg showed that heat-related symptoms are common in these structures [21]. The authors postulate that improving these structures would increase comfort for scholars and could raise educational outcomes.…”
Section: Response To Extreme Weather Events and Gradual Increments Inmentioning
confidence: 99%
“…Impacts, including measurable mortality effects, are heightened in those living in informal settlements, where houses are often constructed of sheets of corrugated iron [18][19][20]. In addition, heat increments are pronounced in many schools and health facilities as these have not been constructed to withstand current and future temperature levels [21,22]. Importantly, all the impacts of climate change affect mental health, in a nation where already one sixth of the population have a mental health disorder [23].…”
Section: Introductionmentioning
confidence: 99%
“…[32] In one study in Johannesburg, which has a relatively mild climate, temperatures reached as high as 47.5°C in the containers and the large majority of students reported experiencing heat-health symptoms every day, including drowsiness, poor concentration and thirst. [33] These impacts will be even greater in hotter regions of the country, such as Northern Cape and Limpopo provinces. A study in Cameroon had similar findings, with notably higher symptoms among girls than boys.…”
Section: Guest Editorialmentioning
confidence: 99%